DESAIN & PERANCANGAN ALAT PEMISAH KUALITAS BUAH JERUK LEMON OTOMATIS - Agung Dwi Sapto (Asosiasi Dosen Muda Indonesia, 2024)
The process of sorting fruits at this time still uses conventional methods, namely the use of human labor (manual). Therefore, a system is needed that can carry out the sorting process automatically in a short time. The purpose of this study is to determine the components of the lemon quality separator along with its automation system and the distribution of static loading on the frame of the lemon quality separator. The automation system used is a TCS3200 sensor (green / yellow color selection) and a photodiode sensor (large / small lemon size). The frame construction was designed using solidworks 2018 software. Material used in hollow iron frame (ASTM A36). Based on the results of the study showed that the maximum voltage on the frame (frame) is 2.470 MPa and the minimum is 0.100 MPa. The maximum value at displacement is 0.027 mm, and the minimum value at safety of factor is 82.582.